Antigua and Barbuda : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
Antigua and Barbuda's 2004 Article IV Consultation reports that growth has strengthened since mid-2003 owing to a rebound in tourism, but fiscal imbalances remain large, the debt stock is high, and arrears continue to mount. Tourism has rebounded strongly as the global economy strengthens and security concerns eased. Fiscal imbalances narrowed modestly, in large part owing to expenditure compression as financing constraints tightened. The administration has reiterated its campaign pledge to return normalcy to fiscal and debt relations, and improve governance and transparency.